Kinetic Insights into Solar-Assisted Fabrication and Photocatalytic Performance of CoWO4/NCW Heterostructure - Hassan, Ali Abed; Shakir, Ibtehal Kareem (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
This work studies the kinetic model for the solar-driven fabrication of CoWO4/NCW heterostructure photocatalysts and investigates their enhanced photocatalytic degradation activity. The synthesis of CoWO4/NCW, its characterization, and the kinetic aspects of photocatalytic degradation under solar light. New nanocomposite prepared from Nano cellulose (NCW) by hydrolysis cotton waste (CW) by nitric acid and cobalt tungstate (CoWO4) prepared from sodium tungstate and cobalt chloride by wet chemical method and characterized through XRD, FTIR, EDX, and FE-SEM analyses. The composite's performance in organic oxidation from refinery wastewater (RWW) was evaluated under solar light. The high removal ratio was 97.4% for organic pollutants (OP) in refinery wastewater. The results indicate that the heterostructure exhibits improved photocatalytic performance compared to individual components, which kinetics model was the best to represent the photocatalytic degradation of organic pollutants from oily wastewater over the heterostructure CoWO4/NCW catalyst. Add future applications of this finding in the relevant industries. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).